From the Eye to the Heart: Association between Age-Related Macular Degeneration and Cardiovascular Disease (a Systematic Review): Oral Presentation - Observational Study - General practitioner - Sausan; Presialia, Athira; Khalifah, Rasyad; Adriono, Gitalisa Andayani (Ophthalmologica Indonesiana, 2024)
Introduction & Objectives Age-related macular degeneration (AMD) is the third leading cause of global blindness, while cardiovascular disease (CVD) is recognized as a major cause of morbidity and mortality. Both are complex diseases associated with aging. It has recently been argued that there is an association between AMD and CVD. This study examined whether AMD increased the risk of CVD and/ or CVD mortality. Methods A systematic review was conducted through three databases (Pubmed, Scopus, and Embase) for relevant studies published between 2016-2023. We selected studies which focused on subjects with AMD, regardless of stages, and their risks for developing CVD and/or CVD mortality. Results Two cohort studies and one case-control study are included, involving 93.388 patients aged >40 years old. One cohort study found that subjects with choroidal neovascularization were associated with an increased rate of cardiovascular mortality (HR 3.16 95% CI 1.62-6.15). Another study also found that AMD was associated with a 1.58 fold increased risk of heart failure (adjusted OR, 1.56; 95% CI, 1.16–1.87; P<0.001) after adjustment for confounders. Moreover, aside from the variables on which this systematic review focused on, the cohort studies also found AMD correlation with other diseases and causes of mortality. Conclusion Individuals with AMD have higher risk for developing CVD. Thus, screening for AMD may be beneficial in preventing CVD.